The Integration and Interconnection of Knowledge In Aceh: A Historical Perspective - Mulyadi Mulyadi; Nur Balqis; Miswari Miswari; Ridwan Ridwan (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2025)
This article aims to analyse the history of the integration of religious knowledge and general knowledge in Aceh. The focus of the analysis is on the classical period, the modern period, and the contemporary period. The research approach uses the historical method by conducting: Topic selection, namely the history of the integration-interconnection of religious and general sciences in Aceh; Source collection, namely collecting materials or literature sources related to the research subject; Verification, namely testing the authenticity and credibility of materials or sources; Interpretation, namely analyzing and synthesizing sources, and; Writing, namely writing the selected topic, the history of the internalization of knowledge in Aceh. This research is based on the concept of integration and interconnection of knowledge initiated by M. Amin Abdullah, with a focus on its application to religious and general knowledge in Aceh. The results of the study show that in the classical period, influenced by certain political forces, some educational institutions made philosophical Sufism a hardcore science, and others made theological studies a hardcore. In the modern and contemporary periods, madrasas made monotheism knowledge as a hardcore science.